(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To investigate the normative handgrip strength of healthy adult male and female Pakistani population and to compare it with consolidated norm. Methodology: It was a survey-based study included 365 healthy Pakistani adult males and females ages between 18 to 54 years. A calibrated handheld Jammer Dynamometer was used to measure handgrip strength under American Society of Hand Therapists (ASHT) guidelines. Three trials were done alternately from both hands and mean were taken separately as a score. Results: The independent T test showed significant difference among male and female handgrip strength. The strong positive correlation was found between right v/s dominant handgrip strength (r= 0.93) and left v/s non-dominant handgrip strength (r=0.93). When comparing the Pakistani norms with consolidated norms the scores were found 30.8% lesser in males and 24.1% lesser in females. Conclusion: The study concluded that the Handgrip strength could be useful to assess and treat the hand functions. It also provides the information that the normative data of handgrip strength may vary among populations with different anthropometric traits. Keywords: Handgrip strength, dynamometer, hand assessment, occupational therapy, normative data, Pakistani population.